Controlled Cooling for Synthesis of Cs2AgBiBr6 Single Crystals and Its Application for X‐Ray Detection. Issue 19 (21st June 2019) - Yin, Lixiao; Wu, Haodi; Pan, Weicheng; Yang, Bo; Li, Penghua; Luo, Jiajun; Niu, Guangda; Tang, Jiang
Abstract: Cs2 AgBiBr6 double perovskite recently emerges as a promising semiconductor for ionization detections because of the low detection limit and nontoxic composition. However, it suffers from unsatisfactory reproducibility and wide fluctuation of electrical properties, as also in other halide perovskite systems. Here, solubility and supersolubility are employed as quantitative indicators to direct the growth of Cs2 AgBiBr6 single crystals. The optimized Cs2 AgBiBr6 crystals exhibit smooth surface as well as high resistivity with narrow distribution from 6.10 × 10 9 to 3.31 × 10 10 Ω cm, in contrast to the unoptimized Cs2 AgBiBr6 crystals ranging from 6.04 × 10 7 to 5.61 × 10 9 Ω cm. Moreover, the fabricated X‐ray detector has a sensitivity of 1974 µC Gyair −1 cm −2 under 50 V mm −1 electric field, which is close to lead halide perovskite detectors. This study highlights the importance of quantitative understanding about the growth process, and might also be applicable to other crystal growth methods, for instance, antisolvent or solvent evaporation method. Abstract : The optimized Cs2 AgBiBr6 single crystal exhibits good performance as X‐ray detector . The synthesis process is optimized according to the solubility versus temperature curves. The optimized Cs2 AgBiBr6 crystals achieve high resistivity with narrow distribution from 6.10 × 10 9 to 3.31 × 10 10 Ω cm. The fabricated X‐ray detector reaches a sensitivity of 1974 µC Gyair −1 cm ‐2 .